Demographics, Social Media Usage, and Political Engagement in Punjab - Kaur, Manpreet; Verma, Rajesh (Indian Journal of Marketing, 2018)
Digital media has played a vital role in mobilizing voters, especially youth in Western countries. Based on a survey conducted in Punjab among different age groups, the current study focused on influence of social media usage on political engagement during the 2017 Legislative Assembly Elections in Punjab, India. Regression analysis and other descriptive analysis were deployed in order to get the results, where the current study highlighted the change in political scenario due to utilization of social media in Punjab. On analyzing the data, social media was found to be the most frequently used source to get political information in the 2017 Legislative Assembly Elections. In fact, during the same period, getting news through newspapers and television were considered as other important sources. Further, social media usage for political purposes was found to have a significant positive influence on political engagement. The results of the study provided empirical evidence of online political engagement as well as contributed to the academic literature with reference to impact of social media usage on political engagement in the Indian context, which will help practitioners, political leaders, and parties in formulation of marketing strategies.